Peningkatan Ketrampilan Pengelolaan Kesehatan Menstruasi Di SMA Negeri 1 Kramat - Umriaty Umriaty; Reni Eka Saputri; Ratih Sakti Prastiwi; Intan Cristy Mayasari (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Menstruation is an important event in the life cycle of adolescent. Therefore it is important to make adolescent understand how and how to deal with menstruation. One of the efforts to realize Clean and Healthy Behavior is to manage health during the menstrual period. The provision of health education in this activity aims to bring up positive behavior around managing menstruation. This activity was carried out at SMA Negeri 1 Kramat involving 29 class XI students. The material presented included the process of menstruation, the menstrual cycle, menstrual hygiene, use of pads, Pre Menstrual PMS Syndrome, and dysmenorrhea. The methods used in this activity are lectures, questions and answers, and demonstrations. Yoga exercise to reduce dysmenorrhea is delivered using a demonstration method which is directly practiced by students. In addition to providing health education, this activity also initiated the availability of pads, drugs to treat menstrual pain and iron tablets at the School Health Unit (UKS). The results of the feedback obtained from this activity were that 65.5% of students stated that they were very happy with this activity, 89.7% of students stated that the material presented was very useful, and 100% of students were willing to practice the information provided.